Infrared thermography to select commercial varieties of maize in relation to drought adaptation. Issue 1 (2nd January 2017) - García-Tejero, Iván Francisco; Hernández-Cotán, Almudena; Apolo, Orly Enrique; Durán-Zuazo, Víctor Hugo; Portero, Manuel Aguilar; Rubio-Casal, Alfredo Emilio
Abstract: Water is the most limiting factor for irrigated agriculture in many areas of South Europe. Within the strategies to maintain agriculture as a sustainable activity, the selection of crop varieties with a high adaptation capacity to water stress situations is crucial. Leaf temperature is a feasible indicator of the crop-water status, being the thermography a non-destructive tool to quantify plant physiological status. The aim of this study was to define the robustness of thermal imaging as a tool for selecting maize ( Zea mays L.) varieties for drought tolerance. The trial was conducted using young plants of five commercial varieties, which were subjected to two different watering situations (well watered and water stressed). Every 48–72 h, thermal images were taken in four plants per irrigation treatment and variety. With the same periodicity and number of plants, stomatal conductance, leaf-water potential and chlorophyll fluorescence measurements were done to assess the impact of water stress in terms of crop physiological status. Our results allowed conclude that infrared thermography could be a useful method for screening procedure in selecting maize varieties for drought adaptation.